Survey on fault tolerance‐based clustering evolution in WSN. Issue 4 (1st July 2020) - Mohapatra, Hitesh; Rath, Amiya Kumar
Abstract : On‐going research on remote communication and sensing essentially made accessible the flexible technology called 'wireless sensor network (WSN)', which is independent, self‐organising and self‐healing in nature. The WSN comprises an extensive number of homogeneous or heterogeneous sensor nodes that may be deployed in a uniform or non‐uniform manner in a targeted zone. The organisation of WSN can be stretched out from residential to a harsh and hostile environment. The manageability of WSN is very subjective to an efficient adaptation to the failure situations. In this line of thought, clustering has been proven as an efficient strategy for prolonging the sensor network lifetime and selecting the correct topological structure for the sensor network. The authors' first present a survey of existing survey works from 2002 to 2019 and then present a tutorial on existing fault‐tolerant protocols with a comparative analysis. The target audience of this work is novice researchers in the field of WSN to get a preliminary idea about clustering and its objective.